2014
DOI: 10.1002/anie.201402767
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal‐Free Tunable Chemoselective N Functionalization of Indoles with Ynamides

Abstract: Two unprecedented N functionalizations of indoles with ynamides are described. By varying the electron-withdrawing group on the ynamide nitrogen atom, either Z-indolo-etheneamides or indolo-amidines can be selectively obtained under the same metal-free reaction conditions. The scope and synthetic potential of these reactions, as well as some mechanistic insights provided by DFT calculations, are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 46 publications
1
36
0
Order By: Relevance
“…We have shown that under strongly basic conditions an unprecedented nucleophilic addition of various heteroarenes at the β position could take place . Moreover, depending on the substitution pattern of the nitrogen atom, the same basic conditions could lead to an α‐nucleophilic addition, albeit with the loss of the electron‐withdrawing group (EWG).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that under strongly basic conditions an unprecedented nucleophilic addition of various heteroarenes at the β position could take place . Moreover, depending on the substitution pattern of the nitrogen atom, the same basic conditions could lead to an α‐nucleophilic addition, albeit with the loss of the electron‐withdrawing group (EWG).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, depending on the substitution pattern of the nitrogen atom, the same basic conditions could lead to an α‐nucleophilic addition, albeit with the loss of the electron‐withdrawing group (EWG). In the α‐nucleophilic addition case, base activation would lead to cleavage of the EWG, forming an amide that would eventually evolve toward ketenimine 3 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As detailed in Section 2, pyrimidines are quite unreactive azadienes, but this downside should be balanced by their commercial availability, low cost, and unsurpassed structural diversity in relation to triazines or tetrazines. In addition, the natural charge distribution of the ynamide π‐system would be an excellent match for the pyrimidinyl azadiene. Should the reactivity pitfalls be overpassed, such a [4+2]/retro‐[4+2] sequence would be of relevance to the synthetic community, giving access to libraries of nitrogen‐containing heterocycles 144 possessing relevant exit vectors for further diversification .…”
Section: Inverse‐electron‐demand [4+2] Cycloadditions Between Ynammentioning
confidence: 99%
“…A general method for the synthesis of (Z)-βphosphor-enamides, which can serve as very useful building blocks and ligands, remains unexplored. [20] Very recently, our group discovered that the base-promoted hydroamidation of ynamides is a general synthetic strategy for (Z)-ethene-1,2-diamides with excellent regio-and stereoselectivity. Herein we report an unprece-dented base-promoted hydrophosphorylation of ynamides to furnish diverse unknown (Z)-β-phosphorenamides via the trans-selective β-addition of ynamides ( Figure 2, eq d).…”
mentioning
confidence: 99%